Analysis of laser Doppler flowmetry long-term recordings for investigation of cerebral microcirculation during neurointensive care - Mauritzon, Stina; Ginstman, Fredrik; Hillman, Jan; Wårdell, Karin (Frontiers in Neuroscience, 2022)
Cerebral blood flow is monitored in the neurointensive care unit (NICU) to avoid further brain damage caused by secondary insults following subarachnoid hemorrhage and brain trauma. Current techniques are mainly snap-shot based and focus on larger vessels. However, continuous monitoring of the smaller vessels may help detect the onset of secondary insults at an earlier stage. In this study, long-term measurements of brain microcirculation with laser Doppler flowmetry (LDF) were performed and evaluated. The aim was to identify and describe physiological signal variations and separate these from movement artifacts. Fiberoptic probes for subcortical LDF recordings of perfusion and total light intensity (TLI) were implanted in three patients with subarachnoid hemorrhage. Data were successfully collected and visualized in real-time over 4 days, resulting in 34, 12, and 8.5 h per patient. Visual observation, wavelet transforms, moving medians, and peak envelopes were used to identify and describe movement artifacts and physiological changes. Artifacts occurred in <5% of the total recording time and could be identified through signal processing. Identified physiological signal patterns included a slowly increasing perfusion trend over hours, vasomotion mainly at 2 cycles/min both in the perfusion and the TLI, and rapid, synchronized changes in the TLI and the perfusion on 38 occasions. Continuous LDF recordings indicating changes in the microvascular blood flow can increase the understanding of the microcirculation in the injured brain. In the long run, this may become a complement for the detection of secondary insults at an earlier stage than possible with today’s techniques.